2016
DOI: 10.1186/s12866-016-0730-7
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Salmonella in food and feed by coupling loop-mediated isothermal amplification with bioluminescent assay in real-time

Abstract: BackgroundSalmonella is among the most significant pathogens causing food and feed safety concerns. This study examined the rapid detection of Salmonella in various types of food and feed samples by coupling loop-mediated isothermal amplification (LAMP) with a novel reporter, bioluminescent assay in real-time (BART). Performance of the LAMP-BART assay was compared to a conventional LAMP and the commercially available 3M Molecular Detection Assay (MDA) Salmonella.ResultsThe LAMP-BART assay was 100 % specific am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 39 publications
4
51
0
Order By: Relevance
“…However, the results of this study indicate that an enrichment step is required to increase the number of bacteria to detectable levels. Moreover, our results agreed with previous studies that demonstrated higher sensitivity resulting from addition of a step enrichment for the LAMP assay compared to the conventional LAMP assay without enrichment (Yang, Domesle, Wang, & Ge, ).…”
Section: Discussionsupporting
confidence: 92%
“…However, the results of this study indicate that an enrichment step is required to increase the number of bacteria to detectable levels. Moreover, our results agreed with previous studies that demonstrated higher sensitivity resulting from addition of a step enrichment for the LAMP assay compared to the conventional LAMP assay without enrichment (Yang, Domesle, Wang, & Ge, ).…”
Section: Discussionsupporting
confidence: 92%
“…The reaction time of multiplex real‐time RPA was 20 min, and the temperature is 35°C in our RPA assay. LAMP assays can also be used to detect Salmonella from foods, environmental samples at 60°C ‐65°C within 30–60 min of reaction time (Gong et al, 2016; Hu et al, 2018; Mashooq, Kumar, Niranjan, Agarwal, & Rathore, 2016; Techathuvanan & D'Souza, 2012; Techathuvanan, Draughon, & D'Souza, 2010; Yang, Domesle, Wang, & Ge, 2016; Zhang, Pan, et al, 2012; Zhang, Shan, et al, 2012). Zhang, Shan, et al (2012) developed a method for detection of Salmonella in food with a LOD for pure culture of 16 CFU/reaction and a sensitivity in food samples of 93.6%.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP was coupled with BART and this novel method was compared with routine LAMP and 3M MDA Salmonella methods for the rapid detection of Salmonella ( invA gene) in meat products (Yang and others ). S. enterica serovar Typhimurium LT2 was used for assay development and sensitivity testing, whereas S. enterica serovars Heidelberg 1364 H (ground turkey) and Typhimurium LT2 (ground beef) were used for the spiking of meat products.…”
Section: Advances In Lamp Methods For Quality Assessment Of Meat Prodmentioning
confidence: 99%
“…The concentration of original target DNA is determined by the time needed to reach peak light output, thereby it provides real‐time quantification (Gandelman and others ). Yang and others () coupled the LAMP method with a bioluminescent assay in real‐time (BART) monitoring of Salmonella in food and feed samples. They reported a high correlation ( R 2 = 0.941–0.962) between Salmonella cell numbers and LAMP‐BART signals, indicating the higher efficacy of the developed method.…”
Section: Loop‐mediated Isothermal Amplificationmentioning
confidence: 99%